Finite Element Analysis of Patient Specific Bone Plate with Ti6Al4V Material Selection - Dita Ayu Mayasari; Talitha Asmaria; Safarudin Ramdhani; Muhammad Satrio Utomo; Daniel Panghihutan Malau; Dhyah Annur; Muhammad Ikhlasul Amal; Ika Kartika (Universitas Negeri Surabaya, 2021)
A patient-specific implant is a designed implant that considers the needs of a specialized patients condition. In several surgical cases, the implant design needs to be adjusted based on the patient bones surface to suit the bone morphometry. This study aims to conduct the finite element analysis to investigate the stress distribution alongside the plate to consider clinical implementation. A bone plate has been designed following an adult pelvic bone shape for the pelvic fractures clinical case management. An FEA was accomplished to analyse the implant designs performance and estimate the installations clinical failures before the manufacturing process. The FEA calculation achieved the highest number of von misses stresses (VM) on the pelvic bone plate by 3.616 MPa. The obtained VM number on the simulation is smaller than the yield strength of Ti6Al4V. It concludes that the customized iliac plates design using Ti6Al4V can have excellent mechanical strength and can withstand the loading. Additional similar simulation using another software strengthen the results.